Financing social entrepreneurship in the Arab world: the case of Lebanon. (1st January 2014) - Chahine, Teresa; Farhat, Zeina
Among the Arab countries, Lebanon has among the most established civic sectors, providing social goods and services in underserved communities. While donations and grants decline, social entrepreneurship is gaining momentum. We propose the use of loans to build social enterprises, and present the results of interviews and discussions with established and aspiring social entrepreneurs. Our observations indicate that there is a market for loans in the social sector, depending on key factors including the organisation's financial maturity and the ability to overcome the cultural fear of loans. It is likely that similar patterns will be observed in other Arab countries, but further studies are needed.